Pola Makan dan Faktor-faktor yang Mempengaruhi Status Gizi Anak Balita di Posyandu Jakarta Utara - Bernadetha Beatrix Sibarani; Made Astawan; Nurheni Sri Palupi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
One of the methods that can be used to determine Under Five Years Old Children’s (UFYOC) diet is 24 hours dietary recall, which furtherly processed using Nutrisurvei program to obtain the values of energy, protein, fat, carbohydrate, iron, calcium, phosphorous, also vitamin A, C, and D. Nutrition value will be compared with 2013 recommended dietary allowance and be used to determine nutritional status for each age group. Nutritional status was measured by referring to weight for age (BB/U) and upper arm circumference (LILA/U). 70 UFYOC respondents from two Posyandus in North Jakarta were involved. Selected Posyandu represented two social demography conditions. Data analysis were obtained using Chi-square correlation. The confidence level used was 95%. Regression analysis used was logistic regression. Weight for Age (BB/U) was a dependent variable, while independent variable consisted of maternal nutritional knowledge, food expenses, nutrition (energy, protein, fat, carbohydrate, iron, calcium, phosphorous, also vitamin A, C, and D), maternal education level and occupation. Finally, there was a significant relationship among nutritional status of UFYOC with maternal nutritional knowledge, food expenses, iron intake, and vitamin D intake and maternal education level. Therefore, the equation model obtained was R2 19.5%.